Analisis Faktor yang Mempengaruhi Minat Mahasiswa dalam Investasi di Pasar Modal Syariah - Widya Widya; Devi Yulia; Dini Selasi (Jurnal Syntax Admiration, 2024)
The Islamic capital market in Indonesia has experienced significant growth in recent years, mainly due to the support from the government and Islamic financial institutions. Increased awareness of the importance of investments in accordance with Islamic principles is one of the main drivers of this growth. In addition, the existence of various investment products such as sharia stocks, sukuk, and sharia mutual funds that are in accordance with sharia principles is increasingly attracting the interest of the public, including students. This study aims to analyze the factors that affect students' interest in investing in the sharia capital market. The method used is systematic literature review, research data is taken from various literature and related studies, and shows that these factors have a significant influence on students' interest in investing in the Islamic capital market. This research is expected to contribute to increasing student participation in sharia investment and increasing financial literacy among the younger generation. The results of the study show that good financial literacy, strong internal motivation, social support from the surrounding environment, and easy access to sharia investment technology have a significant influence on student interest. User-friendly digital platforms and access to training also make it easier for students to start sharia investment.